Static allometry of a threat device that is not a weapon: wing spots in male Heterandrium fallax (Hymenoptera Agaonidae). Issue 2 (4th March 2023) - Eberhard, William G.; Rodríguez, Rafael L.
Abstract : Males of the agaonid wasp Heterandrium fallax have wing spots that they display during aggressive encounters near the ostioles of syconia of the fig Ficus pertusa, apparently in competition for the opportunity to copulate with emerging females. In accord with predictions of the "functional allometry hypothesis" for the allometry of structures that are under sexual selection as threat devices and that do not function as weapons, larger males tended to have proportionally larger wing spots. Some smaller males lacked spots, and smaller males were less likely to be collected near female emergence sites or to show antennal damage that probably results from male fights.